Effect of Degeneration on Fluid–Solid Interaction within Intervertebral Disk Under Cyclic Loading – A Meta-Model Analysis of Finite Element Simulations - Nikkhoo, Mohammad; Khalaf, Kinda; Kuo, Ya-Wen; Hsu, Yu-Chun; Haghpanahi, Mohammad; Parnianpour, Mohamad; Wang, Jaw-Lin (Frontiers in Bioengineering and Biotechnology, 2015)
The risk of low back pain resulted from cyclic loadings is greater than that resulted from prolonged static postures. Disk degeneration results in degradation of disk solid structures and decrease of water contents, which is caused by activation of matrix digestive enzymes. The mechanical responses resulted from internal solid–fluid interactions of degenerative disks to cyclic loadings are not well studied yet. The fluid–solid interactions in disks can be evaluated by mathematical models, especially the poroelastic finite element (FE) models. We developed a robust disk poroelastic FE model to analyze the effect of degeneration on solid–fluid interactions within disk subjected to cyclic loadings at different loading frequencies. A backward analysis combined with in vitro experiments was used to find the elastic modulus and hydraulic permeability of intact and enzyme-induced degenerated porcine disks. The results showed that the averaged peak-to-peak disk deformations during the in vitro cyclic tests were well fitted with limited FE simulations and a quadratic response surface regression for both disk groups. The results showed that higher loading frequency increased the intradiscal pressure, decreased the total fluid loss, and slightly increased the maximum axial stress within solid matrix. Enzyme-induced degeneration decreased the intradiscal pressure and total fluid loss, and barely changed the maximum axial stress within solid matrix. The increase of intradiscal pressure and total fluid loss with loading frequency was less sensitive after the frequency elevated to 0.1 Hz for the enzyme-induced degenerated disk. Based on this study, it is found that enzyme-induced degeneration decreases energy attenuation capability of disk, but less change the strength of disk.